MECANIZAÇÃO DA COLHEITA DE PLANTAS AROMÁTICAS E MEDICINAIS NA AGRICULTURA FAMILIAR - Valdiero, Antonio C.; Andrighetto, Pedro L.; Gilapa, Genaro M. M.; Viau, Luiz V. M.; Sackser, Gilberto; Souza, Maurício d.; Gonçalves, Alexandre (Salão do Conhecimento, 2013)
Resumo